Association between self‐reported urinary incontinence and musculoskeletal conditions in community‐dwelling elderly women: A cross‐sectional study. Issue 4 (28th January 2014) - Kim, Hunkyung; Yoshida, Hideyo; Hu, Xiuying; Saito, Kyoko; Yoshida, Yuko; Kim, Miji; Hirano, Hirohiko; Kojima, Narumi; Hosoi, Erika; Suzuki, Takao
<x xml:space="preserve">Abstract</x> Aims Urinary incontinence (UI) and musculoskeletal conditions, particularly low back pain (LBP), and osteoarthritis (OA), are common problems that have been associated with mobility limitations and future dependence in activities of daily living in the elderly. The purpose of this study was to explore the relationship between UI, UI types, and musculoskeletal conditions in elderly community‐dwelling women. Methods A cross‐sectional study was performed on 1, 399 community‐dwelling Japanese women aged 75–84 years. Face‐to‐face interviews, body composition, and physical function, including grip strength, and usual walking speed, were conducted. UI was defined as experience of urine leakage episodes more than once per week. Self‐reported presence and degree of pain, LBP, and OA were assessed. Student's t‐tests and chi‐square tests were used to analyze continuous and categorical variables. Associations between selected variables, UI, and UI types were assessed using stepwise multiple logistic regression models. Results A total of 260 participants had UI (18.6%) and 399 had LBP (28.5%). Participants with UI were more likely to experience pain (76.0%) and LBP (36.2%) than those without UI (P < 0.001 and P = 0.002, respectively). Age, body mass index, falls, walking speed, grip strength, LBP, and pain coupled with OA were significantly associated with UI. There were significant associations between urge UI and mild (odds ratio (OR) = 1.653, 95% confidence interval (CI) = 1.031–2.650) and severe LBP (OR = 2.617, 95% CI = 1.193–5.739). Conclusions This study showed that UI was significantly associated with musculoskeletal conditions, including LBP, and the combination of pain and OA. The risk of urge UI was greater with increasing severity of LBP. Neurourol. Urodynam. 34:322–326, 2015. © 2014 Wiley Periodicals, Inc.